Effectiveness of coca tea to reduce work stress in the administrative staff in a university - Rivera-Encinas, María Teresa (2016)
Objetive: To evaluate the effectiveness of coca tea to reduce work stress in the administrative staff in a university. Material and methods: The questionnaire for the detection of work stress of the ILO / WHO was applied to two groups of workers, experimental (10) and control (10) using a simple randomization. A cross over experiment was done in 31 days using coca tea and water for each group. Wilcoxon analysis was used to compare groups before and after the test, and the U Mann Whitnney test was used to compare the experimental and control groups. Results: Decrease of work stress was found in the score of the group who drank coca tea (from 71,2 to 68,6), but was not statistically significant (p> 0,05). Administrative staff features with job stress were: 55% female; 60% had 5 years or more of service; 90% worked more than 8 hours per day; 25% performed meditation and 60% performed physical activity. Conclusions: Tea coca is not effective to reduce work stress. More studies are needed. To improve mental health at work is recommended to use interventions and making guides to reduce work stress.